Encouraging Landscape Water Conservation Behaviors Series Overview #7: Personal and Social Norms of Florida Residents Who Use Irrigation in the Home Landscape - Anil Kumar Chaudhary; Laura A. Warner; Alexa Lamm; Joy N. Rumble; Randall Cantrell (EDIS, 2015)
This 4-page fact sheet is the seventh publication in the Encouraging Landscape Water Conservation Behaviors series, which focuses on encouraging water conservation among Florida residents who use irrigation in their home landscapes. Extension educators create programs to encourage good irrigation practices and water conservation activities based on personal and social normative beliefs. To help in this goal, the authors examine personal and social norms of Florida residents who use irrigation in the home landscape and describe how Extension educators can capitalize on these positive norms to motivate Floridians to learn and use best water conservation practices. Written by Anil Kumar Chaudhary, Laura A. Warner, Alexa Lamm, Joy N. Rumble, and Randal Cantrell, and published by the Agricultural Education and Communication Department, September 2015.